2022
DOI: 10.1093/g3journal/jkac222
|View full text |Cite
|
Sign up to set email alerts
|

The mIAA7 degron improves auxin-mediated degradation inCaenorhabditis elegans

Abstract: Auxin-inducible degradation (AID) is a powerful tool for the targeted degradation of proteins with spatiotemporal control. One limitation of the AID system is that not all proteins are degraded efficiently. Here, we demonstrate that an alternative degron sequence, termed mIAA7, improves the efficiency of degradation in C. elegans, as previously reported in human cells. We tested depletion of a series of proteins with various sub-cellular localizations in different tissue types and found that the use of the mIA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…2B,F). These ambiguities could be addressed in future studies by creating and/or combining conditional null alleles using the auxin-inducible degron (AID) system (Ashley et al, 2021; Hills-Muckey et al, 2021; Martinez et al, 2020; Negishi et al, 2021; Sepers et al, 2022; Xiao et al, 2023; Zhang et al, 2015) or an analogous approach (Nance and Frøkjær-Jensen, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…2B,F). These ambiguities could be addressed in future studies by creating and/or combining conditional null alleles using the auxin-inducible degron (AID) system (Ashley et al, 2021; Hills-Muckey et al, 2021; Martinez et al, 2020; Negishi et al, 2021; Sepers et al, 2022; Xiao et al, 2023; Zhang et al, 2015) or an analogous approach (Nance and Frøkjær-Jensen, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The auxin-inducible degron (AID) system enables rapid degradation of C. elegans proteins ( Ashley et al, 2021 ; Hills-Muckey et al, 2021 ; Martinez et al, 2020 ; Negishi et al, 2022 ; Sepers et al, 2022 ; Zhang et al, 2015 ). It requires a minimal AID tag on the protein of interest (POI), expression of the Arabidopsis F-box protein TIR1, and exogenous exposure to the plant hormone auxin.…”
Section: Resultsmentioning
confidence: 99%
“…In Caenorhabditis elegans , higher protein degradation efficiency was seen with mIAA7 than with AID* ( Sepers et al, 2022 ). Though derived from different A. thaliana IAA response transcription repressor proteins (IAA7 vs. IAA17), and differ in primary sequences, both mIAA7 (IAA7 37-104) and AID* (IAA17 71-114) degrons contain the conserved domain II F-box protein binding motif, yet the former has a longer amino-terminal extension (which was reported to be important to TIR1-mediated protein degradation in plants) and contains no putative ubiquitination sites (and hence the degron tag itself is not ubiquitinated) ( Sepers et al, 2022 ). The mIAA7 degron was first reported by Li et al (2019) and was shown to be an optimal degron to pair with the A. thaliana AFB2 F-box protein to enable protein degradation.…”
Section: Discussionmentioning
confidence: 99%
“…The mIAA7 degron was first reported by Li et al (2019) and was shown to be an optimal degron to pair with the A. thaliana AFB2 F-box protein to enable protein degradation. Sepers et al (2022) used mIAA7 in combination with AtOsTIR1 F79G in their AID system. In the present study, we showed that mIAA7 worked well in combination with OsTIR1 F74A and either 5-Ad-IAA or 5-Ph-IAA in inducing rapid auxin-dependent protein degradation in Y. lipolytica .…”
Section: Discussionmentioning
confidence: 99%